Neuromesodermal Progenitors: A Basis for Robust Axial Patterning in Development and Evolution - Sambasivan, Ramkumar; Steventon, Benjamin (Frontiers in Cell and Developmental Biology, 2021)
During early development the vertebrate embryo elongates through a combination of tissue shape change, growth and progenitor cell expansion across multiple regions of the body axis. How these events are coordinated across the length of the embryo to generate a well-proportioned body axis is unknown. Understanding the multi-tissue interplay of morphogenesis, growth and cell fate specification is essential for us to gain a complete understanding how diverse body plans have evolved in a robust manner. Within the posterior region of the embryo, a population of bipotent neuromesodermal progenitors generate both spinal cord and paraxial mesoderm derivatives during the elongation of the vertebrate body. Here we summarise recent data comparing neuromesodermal lineage and their underlying gene-regulatory networks between species and through development. We find that the common characteristic underlying this population is a competence to generate posterior neural and paraxial mesoderm cells, with a conserved Wnt/FGF and Sox2/T/Tbx6 regulatory network. We propose the hypothesis that by maintaining a population of multi-germ layer competent progenitors at the posterior aspect of the embryo, a flexible pool of progenitors is maintained whose contribution to the elongating body axis varies as a consequence of the relative growth rates occurring within anterior and posterior regions of the body axis. We discuss how this capacity for variation in the proportions and rates of NM specification might have been important allowing for alterations in the timing of embryo growth during evolution.